A dual-functional benzobisthiadiazole derivative as an effective theranostic agent for near-infrared photoacoustic imaging and photothermal therapy - Huang, Shuo (2016)
It is essential to monitor and understand the diseased tissue before starting the treatments. Recently, many efforts have been devoted to explore theranostic agents that encapsulate therapeutic agents and diagnostic probes into one package. However, these physically mixed two agents may slowly dissociate from the carrier at different rates during the circulation in blood, leading to quite different biodistribution and pharmacokinetics. Thus, it is important to explore a photothermal agent which itself can serve as a contrast agent. Though some inorganic dual functional theranostic agents such as gold nanoparticles have been explored, most of them still suffer from poor biodegradability and biocompatibility. Herein, we report a theranostic agent based on a narrow-‐bandgap small molecule, benzo[1,2-c;4,5-c’]bis[1,2,5]thiadiazole-4,7-bis(9,9-dioctyl-9H-fluoren-2-yl)thiophene (denoted as BBT-2FT), with strong absorption of near infrared (NIR) light. Colloidal nanoparticles composed of BBT‐2FT show photoacoustic signal intensity 10 times higher than that of blood, and high photothermal conversion efficiency (η=40%) under irradiation of 800-nm laser light that kills over 90% HeLa cells in 10 mins.